2018
DOI: 10.15282/ijame.15.4.2018.5.0442
|View full text |Cite
|
Sign up to set email alerts
|

Passive Control of Nanoparticles on MHD Jeffrey Nanofluid past a Convectively Heated Moving Plate with Thermal Radiation

Abstract: A theoretical study is conducted to investigate the thermal radiation effect on boundary layer flow of magneto-hydrodynamic (MHD) Jeffrey nanofluid across a moving plate with convective boundary condition. More physically acceptable model of passively controlled wall nanoparticle concentration is executed. Similarity transformation variables are utilised to transform the partial differential equations to non-linear ordinary differential equations. An effective Runge-Kutta Fehlberg Fourth-Fifth order (RKF45) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…for different values of Prandtl number when 1 → ∞, = = 2 = 2 = = = = = = = 0. This comparison has clearly certified the authenticity of the numerical results where the present results generated with the help of Maple are in a good agreement with those of Mohamed et al, [21], Bataller [22], Roşca and Pop [25] and Zokri et al, [12]. Figure 2 and 3 are plotted to examine the outcome of magnetic parameter, on the profiles of temperature and concentration.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…for different values of Prandtl number when 1 → ∞, = = 2 = 2 = = = = = = = 0. This comparison has clearly certified the authenticity of the numerical results where the present results generated with the help of Maple are in a good agreement with those of Mohamed et al, [21], Bataller [22], Roşca and Pop [25] and Zokri et al, [12]. Figure 2 and 3 are plotted to examine the outcome of magnetic parameter, on the profiles of temperature and concentration.…”
Section: Resultssupporting
confidence: 86%
“…Numerical approach via Runge-Kutta Fehlberg method encoded in Maple software is tackled to solve the initial and boundary value problems given in Eq. (8)- (12). The entire investigation is directed to the aftermaths of flow field, temperature, and nanoparticle concentration profiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental works on nanofluids also have been documented by Ahmadi and Willing [9], Masuda et al [10], Das et al [11] and Pak and Cho [12]. Meanwhile, study via a mathematical approach with various effects and surfaces was reported in work done by Kuznetsov and Nield [13], Mahat et al [14], Zokri et al [15] and Waini et al [16].…”
Section: Introductionmentioning
confidence: 86%
“…Ramzan et al, [16] focused on the Jeffrey fluid flow over an inclined stretched cylinder with suspended nanoparticles and investigated the combined impacts of thermal and concentration stratification, thermal radiation, and heat generation/absorption. Meanwhile, Zokri et al, [17] conducted a study to explore the passive control of nanoparticles on MHD Jeffrey nanofluid past a moving plate that was being heated convectively. In line with this, they further their research on Jeffrey fluid flow over a horizontal circular cylinder with suspended nanoparticles and viscous dissipation effect by considering the Buongiorno model [18].…”
Section: Introductionmentioning
confidence: 99%